2001
DOI: 10.1302/0301-620x.83b6.11377
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of bone-marrow oedema of the talus with the prostacyclin analogue iloprost

Abstract: Bone marrow oedema syndrome of the talus is a rare cause of pain in the foot, with limited options for treatment. We reviewed six patients who had been treated with five infusions of 50 microg of iloprost given over six hours on five consecutive days. Full weight-bearing was allowed as tolerated. The foot score as described by Mazur et al was used to assess function before and at one, three and six months after treatment. The mean score improved from 58 to 93 points. Plain radiographs were graded according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(34 citation statements)
references
References 25 publications
2
31
0
1
Order By: Relevance
“…Although the clinical outcome was excellent, the occurrence of temporary side effects, such as nausea, vomiting and headache, was also noted. These beneficial effects of treatment with iloprost in BMES of the femoral head are comparable to those that have been published for the treatment of BMES of the talus,17 metatarsal bone18 and acetabulum 19. Excellent results with very fast recovery have been obtained in all cases of isolated bone marrow edema syndrome lacking signs of necrotic areas 35.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Although the clinical outcome was excellent, the occurrence of temporary side effects, such as nausea, vomiting and headache, was also noted. These beneficial effects of treatment with iloprost in BMES of the femoral head are comparable to those that have been published for the treatment of BMES of the talus,17 metatarsal bone18 and acetabulum 19. Excellent results with very fast recovery have been obtained in all cases of isolated bone marrow edema syndrome lacking signs of necrotic areas 35.…”
Section: Discussionsupporting
confidence: 79%
“…Since 1998, parenterally administered iloprost has been used to treat BMES and early stages of osteonecrosis in our institution 1719. It induces vasodilatation and reduction of capillary permeability and inhibits platelet aggregation 20.…”
Section: Introductionmentioning
confidence: 99%
“…A number of medical therapies have also been undertaken with variable and inconsistent results including the use of calcium channel blockers (nifedipine), prostaglandin infusions, low molecular weight heparin, and statins [118–121]. These pharmacologic agents predominantly ameliorate the regulation of blood supply targeting local ischemia [122] or lipocyte proliferation [120]. More recently, several studies with small number of adult and pediatric subjects have reported the use of bisphosphonates for the treatment of ON [123126].…”
Section: On Prevention and Treatmentmentioning
confidence: 99%
“…In 2001 and 2002, Aigner and colleagues successfully treated patients with bone marrow edema of the forefoot and the acetabulum, not related to renal transplantation or CNI medication, with the stable prostacyclin analogue iloprost (11,12). These trials demonstrated a favorable clinical course, especially when applied early in the time course when overt bone necrosis has not yet occurred.…”
Section: Discussionmentioning
confidence: 99%